PERAN AKUNTANSI AKRUAL DALAM PENYUSUNAN LAPORAN KEUANGAN PADA MASA PANDEMI COVID-19 (Studi Kasus Pada RS. Ortopedi Prof. Dr. R. Soeharso) - Amalla, Atalia Dezy; Bawono, Andy Dwi Bayu (UNIVERSITAS SARI MUTIARA INDONESIA, 2021)
This study aims to determine whether there has been a change in the preparation of financial reports managed by RSO during the Covid-19 pandemic, what obstacles occurred in the preparation of financial reports, what solutions were implemented, the process of implementing accounting management, the application of the accrual accounting system at RSO in the future. the covid-19 pandemic. This study uses interview techniques. The resource persons are the Head of the Accounting Subdivision and BMN, and the Accounting Staff. Data analysis techniques were obtained from interviews, field notes, and documentation. The results of this study indicate that there is no difference in the preparation of financial reports during the Covid-19 pandemic, the constraints faced are related to local accounts received related to the hospital accounting system; assets that have not been registered as well as upgrading the SAIBA application, the solution applied is to revise the SP3B regarding problems received locally; cross-check between budgeting and financial records; using excel with SAIBA templates, the management implementation process was not long before and during the pandemic because RSO used a load master and posting system, and the concept of e-government was implemented in RSO. Keywords: accrual accounting, preparation of financial reports during the Covid-19 pandemic.